Hambatan, Solusi dan Harapan: Pembelajaran Daring Selama Masa Pandemi Covid-19 Oleh Guru Sekolah Dasar - Andri Anugrahana (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2020)
This study aims to determine the problems experienced by teachers during Covid-19 pandemic in which teachers must conduct online learning. This research is a descriptive study using online survey method. The data was collected using online questionnaires to 64 respondents of elementary school teachers. It was found that 98% of the primary school teachers respondents has conducted online learning during Covid-19 pandemic, and 1 teacher did not use online model. The information obtained is that 100% of the teacher is doing online model (in the network) learning. More than 9 medias used by elementary school teachers in Bantul district during the pandemic were offered namely WhatsApps, WhatsApp Web, Google Classroom, Google Group, TeamLink, Microsoft Teams, Kaizala Microsoft, Zoom Meeting & Webinar, Youtube, Google Hangouts, and others. 100% of teachers or as many as 64 teachers are learning with WhatsApps application as the first choice. Furthermore, 15% of teachers use some application supporters of WhatsApp. Google Class is the second option. The third option is Google form as much as 12% or 8 teachers. The use of Google Form is for students’ worksheets. The fourth choice is YouTube with as many as 7% or 5 teachers. Short videos related to the material being taught in 10-20 minutes. The fifth application is the Zoom Cloud Meeting for only 3% or 2 teachers who chose this platform.